A 3-D mid-infrared view of the central parsec. Issue Volume 9:Issue S303(2013) (22nd May 2014) - Moultaka, J.; Eckart, A.; Mužić, K.; Sabha, N.
Abstract: We present a mid-infrared 3D view of the central parsec using ISAAC spectrograph (ESO/VLT) with its spectroscopic mode. We mapped the central parsec in L - and M -bands by using 27 and 21 slit positions, respectively, that allowed us to build two data cubes of the region in these spectral domains. We also use an original method to distinguish the contribution of the foreground extinction to the absorbed spectra from that of the local extinction in both wavelength ranges. We find that there are residual water and CO ices in the central parsec as well as hydrocarbons and gaseous CO implying very low temperatures of the order of tens of Kelvin in the local environment of Sgr A*.